Nomeação rápida e leitura: o que há entre essas duas habilidades? uma revisão sistemática da literatura - Ribeiro, Heloisa Wallau Souto (2024)
Rapid naming is the ability to articulate, as quickly and accurately as possible, the name of visual stimuli presented in a sequence or one at a time. There are evidences that RAN predicts reading performance, and knowing how this occurs could lead to a better understanding of reading mechanisms, the qualification of teaching and the identification of possible learning difficulties, as well as their remediation. However, there is no consensus among researchers on the basis of the relationship between rapid naming and reading. The aim of this study is to carry on a systematic review on research produced between 2015 and 2023 on rapid automatized naming (RAN or NAR – nomeação automatizada rápida) and its relationship with reading. On the purpose of verifying whether research on the topic obtained evidence on these foundations, a search was carried out using the Capes Periodicals portal. Among 199 articles found on the topic of rapid naming, 21 met the inclusion criteria: be peer-reviewed, have as their object the study of the relationship between rapid naming and reading, have neurotypical children or adults as research participants and be published in Portuguese, English, Spanish or French. These studies addressed the brain regions and circuits involved in both rapid naming and reading, the factors involved in the relationship between rapid naming and reading, and the common processes involved in both naming and reading. The results showed that RAN predicts reading because it uses the same brain regions, circuits and processes necessary for reading. Eye movements, attention, working memory, phonological processing, visual processing, motor processing, and the ability to program and coordinate the execution of these processes in a chained manner so that the name of each stimulus is pronounced with speed and accuracy